Relationship between vascular ageing and left ventricular geometry in patients with newly diagnosed primary aldosteronism - Huang, Miao; Li, Jiaying; Zhao, Xiexiong; Chen, Shunsong; Li, Xiaogang; Jiang, Weihong (Frontiers in Endocrinology, 2022)
Background Changes in left ventricular (LV) geometry are early manifestations of cardiac damage. The relationship between vascular aging and LV geometry has been reported. However, in newly diagnosed primary aldosteronism (PA), with more severe target organ damage than essential hypertension, the relationship between vascular aging and LV geometry has never been described. Methods We conducted a retrospective study among newly diagnosed PA from 1 January 2017 to 30 September 2021 at the Third Xiangya Hospital. The data of vascular aging parameters were collected, including ankle–brachial index (ABI), brachial–ankle pulse wave velocity (baPWV), and carotid intima-media thickness (cIMT). Echocardiography data were collected to assess LV geometry patterns. Results A total of 146 patients with newly diagnosed PA were included. The mean age was 44.77 ± 9.79 years, and 46.58% participants were women. Linear regression analysis adjusting all potential confounders showed that cIMT was significantly associated with LV mass index (LVMI) (β=0.164, P=0.028) and baPWV was significantly associated with relative wall thickness (RWT) (β= 0.00005, P=0.025). Multifactorial adjusted logistic regression analysis demonstrated that cIMT was significantly associated with LV hypertrophy (LVH) (OR=7.421, 95%CI: 1.717–815.688, P=0.021) and baPWV was significantly associated with LV concentric geometry (LVCG) (OR=1.003, 95%CI: 1.001–1.006, P=0.017). Conclusion baPWV was significantly associated with LVCG and cIMT was significantly associated with LVH in newly diagnosed PA. This study provides insights on the importance of baPWV measurement and cIMT measurement in early assessment of cardiac damage in newly diagnosed PA.